2019
DOI: 10.1038/s41598-019-43089-7
|View full text |Cite
|
Sign up to set email alerts
|

A combined FSTRA-shotgun proteomics approach to identify molecular changes in zebrafish upon chemical exposure

Abstract: The fish short-term reproduction assay (FSTRA) is a common in vivo screening assay for assessing endocrine effects of chemicals on reproduction in fish. However, the current reliance on measures such as egg number, plasma vitellogenin concentration and morphological changes to determine endocrine effects can lead to false labelling of chemicals with non-endocrine modes- of-action. Here, we integrated quantitative liver and gonad shotgun proteomics into the FSTRA in order to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Furthermore, the induction of Vtg protein synthesis may not have immediately occurred at the early embryonic stage, but rather at the later stages when the yolk sac was almost absorbed; thus, at 4 dph, larvae may have just actively started producing Vtg protein. The abundance of Vtg proteins in larval fish exposed to xenoestrogens has been rarely reported, unlike in their adult counterparts; moreover, recent studies showed organ- and sex-specific proteomic responses of adult fish exposed to endocrine disrupting compounds. , Thus, the use of pooled whole embryos might have diluted the relative abundance levels, resulting in lower DAP. Other dysregulated proteins associated with EE2 exposure are involved in cellular growth, organization and transport, metabolic processes, biosynthetic processes, and development; however, most of these proteins had low differential abundance and are not functionally specific, which may suggest that there was a delayed onset of responses at the proteome level.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the induction of Vtg protein synthesis may not have immediately occurred at the early embryonic stage, but rather at the later stages when the yolk sac was almost absorbed; thus, at 4 dph, larvae may have just actively started producing Vtg protein. The abundance of Vtg proteins in larval fish exposed to xenoestrogens has been rarely reported, unlike in their adult counterparts; moreover, recent studies showed organ- and sex-specific proteomic responses of adult fish exposed to endocrine disrupting compounds. , Thus, the use of pooled whole embryos might have diluted the relative abundance levels, resulting in lower DAP. Other dysregulated proteins associated with EE2 exposure are involved in cellular growth, organization and transport, metabolic processes, biosynthetic processes, and development; however, most of these proteins had low differential abundance and are not functionally specific, which may suggest that there was a delayed onset of responses at the proteome level.…”
Section: Resultsmentioning
confidence: 99%
“…These findings represent an important difference from the observed impairment of female fertility in chemical inhibitor studies in which both aromatase isoforms are inhibited in the body. For example, total aromatase inhibition reduced female fathead minnow ( Pimephales promelas ; 6 ), medaka ( Oryzias latipes ; 7 ) and zebrafish ( 8 ) fecundity. These differences are likely due to the contribution of circulating estrogens produced by the ovaries via Cyp19a1a that function to maintain the integrity of the ovarian state and the reproductive capacity (i.e., fertility) of female zebrafish ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eluted peptides were analyzed on a Thermo Fisher Q Exactive mass spectrometer (Thermo Fisher, Waltham, USA) as described previously. 29 , 30 …”
Section: Methodsmentioning
confidence: 99%
“…For quantitative proteomics, 500 ng combined TMT-labeled peptides were injected replicate wise onto a nanoACQUITY UPLC C18 Trap Column, before being separated on a nanoACQUITY reversed-phase analytical column (Waters, Massachusetts, USA) using a linear gradient from 3 to 97% (v/v) of 90% (v/v) acetonitrile in 0.1% (v/v) formic acid for 170 min with a flow rate of 300 nL/min. Eluted peptides were analyzed on a Thermo Fisher Q Exactive mass spectrometer (Thermo Fisher, Waltham, USA) as described previously. , …”
Section: Methodsmentioning
confidence: 99%